2014
DOI: 10.1021/nn5009353
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Earphones: Entertainment for Both Humans and Animals

Abstract: The human hearing range is from 20 Hz to 20 kHz. However, many animals can hear much higher sound frequencies. Dolphins, especially, have a hearing range up to 300 kHz. To our knowledge, there is no data of a reported wide-band sound frequency earphone to satisfy both humans and animals. Here, we show that graphene earphones, packaged into commercial earphone casings can play sounds ranging from 100 Hz to 50 kHz. By using a one-step laser scribing technology, wafer-scale flexible graphene earphones can be obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 30 publications
3
104
0
Order By: Relevance
“…A further experimental confirmation of the EDF-model in a frequency range up to 50 kHz can be found in the recently published work by Tian et al [31] who used the EDF-model to predict sound pressures for a graphene-based TA-emitter layered on a polyethylene terephthalate (PET) substrate. The authors report a deviation of less than 2 dB between the theoretical EDF-prediction and the experimental results.…”
Section: Resultsmentioning
confidence: 60%
“…A further experimental confirmation of the EDF-model in a frequency range up to 50 kHz can be found in the recently published work by Tian et al [31] who used the EDF-model to predict sound pressures for a graphene-based TA-emitter layered on a polyethylene terephthalate (PET) substrate. The authors report a deviation of less than 2 dB between the theoretical EDF-prediction and the experimental results.…”
Section: Resultsmentioning
confidence: 60%
“…It was found that graphene has a significant flat frequency response in the wide ultrasound range ≈20–50 kHz. Additionally, graphene exhibits ultra‐small heat capacity per unit area (HCPUA), more efficiently converting joule heating to sound waves 94, 95, 96, 97, 98, 99, 100. It has been also reported that single‐layer graphene (SLG) presents the lowest HCPUA,101 demonstrating more efficient than other materials.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…Since then, Ren et al developed a high‐efficiency route for the fabrication of real graphene earphones using laser‐scribed graphene (LSG) 98. As is shown in Figure 9 a, the ultrafast graphene growth was obtained at precise locations by a mask‐free and programmable laser scribing technology.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a series of thermo-acoustic transductions manufactured from different materials such as CNT assemblies [9], aluminum wires array [10,11], graphene [12], silver nanowires film [13], suspended CNT-yarn array on a substrate [14] and individual CNT [15,16], were successively reported. A practical wideband sound frequency graphene earphone was also designed and tested by Tian et al [17]. In addition to the intensively experimental research, a few theoretical studies on thermo-acoustics were also reported, including the modeling of thin-film located on a substrate [18], the CNT * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%